2021
DOI: 10.1039/d1py00688f
|View full text |Cite
|
Sign up to set email alerts
|

A transparent cyclo-linear polyphenylsiloxane elastomer integrating high refractive index, thermal stability and flexibility

Abstract: A new type of cyclo-linear structured high phenyl content siloxane elastomer (Ph-CLS-E) is prepared through “one-pot” hydrosilylation reaction that take advantage of the reactivity differences of the cyclic, linear precursors...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…34 The band at 2138 cm À1 is assigned to the characteristic absorption peak of the Si H bond. 35 Compared with PTDS, the peak at 2138 cm À1 of EPHS is weaker, which indicated that partial contents of the Si H bonds had participated in the addition reaction. Meanwhile, the disappearance of the peak signal at 2138 cm…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…34 The band at 2138 cm À1 is assigned to the characteristic absorption peak of the Si H bond. 35 Compared with PTDS, the peak at 2138 cm À1 of EPHS is weaker, which indicated that partial contents of the Si H bonds had participated in the addition reaction. Meanwhile, the disappearance of the peak signal at 2138 cm…”
Section: Discussionmentioning
confidence: 95%
“…EPHS and ESR-6 have obvious signals at 1410 cm À1 ascribed to the characteristic peak of Si CH 2 34. The band at 2138 cm À1 is assigned to the characteristic absorption peak of the Si H bond 35. Compared with PTDS, the peak at 2138 cm À1 of EPHS is weaker, which indicated that partial contents of the Si H bonds had participated in the addition reaction.…”
mentioning
confidence: 96%
“…No soluble fraction was detected in the swelling test, which validates that all PDMS CLs underwent reaction and crosslinking. The degree of swelling is inversely proportional to the extent of cross-linking; as the cross-linking degree increases, the swelling degree diminishes [11,[39][40][41]. As the content of CL increased, there was a corresponding decrease in the swelling degree.…”
Section: Properties Of Pdms Cross-linked With Si-h Terminated Teos He...mentioning
confidence: 99%
“…[3] Higher RI silicones are normally achieved by incorporating aromatic moieties on the silicone backbone. [4][5][6][7][8] Phenyl compounds are widely available commercially and may contain phenylmethyl-and/or diphenylsilicone monomers, typically in addition to Me 2 SiO monomers as random copolymers or blocks. [9][10][11] Their preparation has been optimized in industry, but using challenging chemistry: arylboranes, Grignard processes etc.…”
Section: Introductionmentioning
confidence: 99%